American nature writing, c. 1985 - 2017: the influences and limits of deep ecology - Platts, Helen (2019)
This thesis is concerned with contemporary American non-fiction nature writing and the environmental and philosophical movement deep ecology. The burgeoning field of ecocriticism has noted that contemporary nature writing challenges anthropocentric attitudes towards nature and favours biocentric relationships with nature. I contend that it is the deep ecology movement, which has been gaining international attention since the 1970s, which influences the biocentric tenor of contemporary nature writing. Throughout this thesis, I explore the origin of deep ecology and the movement in contemporary culture. I suggest that deep ecology is present in contemporary American nature writing, and consider how nature writing presents the limits of deep ecology as a viable solution to the environmental crisis.